Spray-drying of the microalga dunaliella salina: Effects on B-Carotene content and isomer composition - Orset, Sandra (2011)
The effects of spray-drying of the unicellular microalga Dunaliella salina on its B-carotene content and geometric isomer composition have been studied. The efficacy of a range of synthetic and natural antioxidants in preventing degradation of B-carotene has been determined. Losses of B-carotene and isomerization were minimal during processing for both the control (no exogenous antioxidants) and the samples containing butylated hydroxytoluene (BHT) and tert-butylhydroquinone (TBHQ). However, the use of tocopherol-based antioxidants resulted in degradation of 52-72% of B-carotene during the drying process. All dried powders of Dunaliella proved to be unstable during storage in the presence of light and air, with B-carotene degraded according to a first-order kinetic model. Of the antioxidants studied, only TBHQ was successful in significantly minimizing degradation (degradation constants of 0.03 and 0.04 days-1, compared to 0.53 days-1 for the respective control). For control powders and those with BHT added to the feed, the degradation constants were reduced to values between 0.27 and 0.37 days-1 by restricting light and flushing with nitrogen; however, storage in the dark alone had no effect. For more slowly degrading powders having TBHQ added to the feed, it was clear that degradation of â-carotene was influenced by both light and oxygen. During storage the 9-cis isomer of B-carotene was significantly more unstable than the all-trans form. TBHQ was, however, successful in reducing relative losses of this isomer for samples stored in the dark. The results suggest a dominant photodegradative mechanism for the loss of the 9-cis isomer of B-carotene.